Faculty peer coaching in higher education : partnerships to support improved instructional practices - Rainville, Kristin N.; Title, David G.; Desrochers, Cynthia G. (Transforming teaching and learning in higher education., 2023)
"This book serves as a guide to developing, launching, and refining faculty peer coaching initiatives in higher education with the goal of improving instructional practice and student learning outcomes. Informed by research and experience, we scaffold readers as the Many of the current challenges facing institutions of higher education require a shift in thinking and practice across virtually every aspect of the way these institutions operate. The changing nature of college students, along with increased emphasis on student learning outcomes, have institutions seeking to effect improvements in the instructional practices of faculty members. Unfortunately, many of the responses to this need have not focused on lasting change that impacts classroom practice. Rather, one-time fixes, like offering workshops or seminars, have become the most prevalent method of faculty development. While these methods do have a place in faculty development, to create lasting change, they must be part of a wider system of support. Establishing a robust model of faculty peer coaching can accelerate improvement efforts that strive to create higher education classrooms centered on inclusive and equitable teaching practices, which more effectively meet the needs of a more diverse student body. Peer Coaching is a collaborative, reciprocal practice where faculty members observe, reflect, and improve their instructional practices with the goal of improved learning for all students. Research has shown that peer coaching can positively impact teaching practices when coupled with other professional learning. The purpose of this book is to provide a rationale for peer coaching as an effective strategy for faculty development and to provide a model for peer coaching to support in the creation of a robust peer coaching initiative in institutions of higher education. We believe, that peer coaching has the potential for significant culture and community change for faculty members and can result in improved student learning"--